2014
DOI: 10.3109/09513590.2014.887063
|View full text |Cite
|
Sign up to set email alerts
|

The effects of metformin on endothelial dysfunction, lipid metabolism and oxidative stress in women with polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a heterogeneous disorder, which is considered not only a reproductive disease but also a metabolic disorder associated with long-term health risks. The aim of this study was to assess the effects of metformin on insulin resistance, oxidant-antioxidant status, endothelial dysfunction, lipid metabolism and their contribution to the risks of cardiovascular disease in women with PCOS. Fifteen women with PCOS and 17 healthy women were included in this case-control study. Nitric o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…Glucose metabolism and inflammation may not be the only pathomechanisms affected by metformin/NRF2. In fact, other salutary effects have been described for redox (Kocer et al, 2014;Kelleni et al, 2015) and protein homeostasis (Tsai et al, 2017).…”
Section: E Repurposing Instead Of De Novo Drug Discovery and Developmentioning
confidence: 99%
“…Glucose metabolism and inflammation may not be the only pathomechanisms affected by metformin/NRF2. In fact, other salutary effects have been described for redox (Kocer et al, 2014;Kelleni et al, 2015) and protein homeostasis (Tsai et al, 2017).…”
Section: E Repurposing Instead Of De Novo Drug Discovery and Developmentioning
confidence: 99%
“…A few groups of investigators have also explored the relationship of these polymorphisms with PCOS and its related traits (23)(24)(25)(26). Treatment with metformin and hormonal supplements (ethinyloestradiol þ cyproterone acetate) has been shown to increase PON1 activity and subsequently decrease oxidative stress in women with PCOS (27,28). However, to our knowledge, no conclusive study exploring the association of PON1 polymorphisms and its activity with PCOS risk, and their relationship with cardiovascular and metabolic dysfunction is available.…”
mentioning
confidence: 99%
“…For instance, Victor et al [27] showed that IR in PCOS patients enhanced oxidative stress and leukocyte adhesion. Kocer et al [28] demonstrated that metformin improved PCOS, probably by decreasing oxidative stress and improving IR. Consistent with this, we demonstrated that oral administration of HLF significantly suppressed the upregulation of both TNF-α and IL-6 induced by DHEA, which might mechanistically contribute to its preventive effect against PCOS progression.…”
Section: Resultsmentioning
confidence: 99%